A commentary on the letters of M. Cornelius Fronto - Hout, Michael Petrus Josephus van den. (Mnemosyne, Supplements, 1999)
This is the first commentary on the letters of Marcus Cornelius Fronto (c. 90-95 - c. 167). It aims at an extensive grammatical, stylistic and historical interpretation of the letters and the ancient testimonies on Fronto. The author demonstrates where Fronto stands in Latin literature; hence the numerous quotations of parallel, similar and dissentient passages from Fronto and other writers. The letters are written in a pure, simple style, with a great deal of colloquialisms and many a post-classical turn of phrase. The many archaisms show how Fronto as a philologist had a comprehensive knowledge of pre-Cicero Latin. This commentary, based on the Teubner-edition by the author (Leipzig 1988), offers a thorough explanation of Fronto's style and language, e.g. of his archaisms and colloquialisms, identification of the persons mentioned, and the chronology of the letters. Seven elaborate indices complete this book.